Stephen Bantu Biko: An agent of change in South Africa"s socio-politico-religious landscape - Dolamo, Ramathate Tseka Hosea (HTS teologiese studies, 2019)
This article examines and analyses Biko’s contribution to the liberation struggle in South Africa from the perspective of politics and religion. Through his leading participation in Black Consciousness Movement and Black Theology Project, Biko has not only influenced the direction of the liberation agenda, but he has also left a legacy that if the liberated and democratic South Africa were to follow, this country would be a much better place for all to live in. In fact, the continent as a whole through its endeavours in the African Union underpinned by the African Renaissance philosophy would go a long way in forging unity among the continent’s nation states. Biko’s legacy covers among other things identity, human dignity, education, research, health and job creation. This article will have far reaching implications for the relations between the democratic state and the church in South Africa, more so that there has been such a lack of the church’s prophecy for the past 25 years.